2009
DOI: 10.1080/10810730902873935
|View full text |Cite
|
Sign up to set email alerts
|

Using the Extended Parallel Process Model to Explain Physicians' Decisions to Test Their Patients for Kidney Disease

Abstract: A study was conducted to determine the effects of perceived threat and efficacy on physicians' intentions and behavior to test their patients' level of kidney functioning. Guided by the extended parallel process model, 151 physicians completed an initial survey measuring threat to patients (i.e., susceptibility and severity) and efficacy (i.e., response-efficacy and self-efficacy), as well as their current intentions and behavior. One-hundred and twelve of these physicians also completed and returned a follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 16 publications
5
42
0
Order By: Relevance
“…Smalec and Klingle (2000) in an experiment on the effects of an interpersonal message to persuade bulimics to seek help, in which levels of threat and efficacy were manipulated as attributes of the message, found that at high levels of efficacy perceived threat was positively correlated with cognitive message acceptance and behavioral message acceptance. Roberto and Goodall (2009) focused on threat to others and found that the highest behavioral intentions and actual behavior (physicians proscribing kidney tests to their patients) was highest in the high threat-high efficacy group. This study was a survey, so perceptions of both threat and efficacy were measured and then median split was used to create four groups.…”
Section: Resultsmentioning
confidence: 99%
“…Smalec and Klingle (2000) in an experiment on the effects of an interpersonal message to persuade bulimics to seek help, in which levels of threat and efficacy were manipulated as attributes of the message, found that at high levels of efficacy perceived threat was positively correlated with cognitive message acceptance and behavioral message acceptance. Roberto and Goodall (2009) focused on threat to others and found that the highest behavioral intentions and actual behavior (physicians proscribing kidney tests to their patients) was highest in the high threat-high efficacy group. This study was a survey, so perceptions of both threat and efficacy were measured and then median split was used to create four groups.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies found evidence for this proposition (Basil, Basil, Deshpande, & Lavack, 2013; Roberto & Goodall, 2009; Smalec & Klingle, 2000; Terblanche-Smit & Terblanche, 2010; Witte & Allen, 2000; Witte, Berkowitz, Cameron, & McKeon, 1998). For example, in a survey, Roberto and Goodall (2009) used median split to divide respondents into four groups based on their levels of perceived threat and efficacy and found that the high threat/high efficacy group had the highest message acceptance (behavioral intentions and behavior at both the initial and follow-up survey). In an experiment pertaining to safe sexual behavior, Terblanche-Smit and Terblanche (2010) manipulated levels of threat (low, medium, and high) and although they did not manipulate efficacy, measured efficacy was relatively high (e.g., 3.9-4.0 on a 5-point scale).…”
Section: The Extended Parallel Process Modelmentioning
confidence: 98%
“…On the other hand, several studies found evidence against this proposition (Rimal & Real, 2003; Roberto & Goodall, 2009; Witte, et al, 1993). In a survey, Witte et al (1993) found that when efficacy was low, greater defensive avoidance, perceived manipulation, and issue derogation were exhibited in the low threat group.…”
Section: The Extended Parallel Process Modelmentioning
confidence: 99%
“…Morrison focused on personal relationships, finding that men could be motivated to speak to women they care about regarding sexual assault through the use of indirect fear appeal messages. Roberto and Goodall (2009) examined physician-patient relationships, finding that primary care physicians perceiving greater efficacy and threat to patients were more motivated to test their patients for kidney disease. Finally, Goei and colleagues (2010) studied an asthma intervention in K-8 level schools and demonstrated the efficacy of educating school workers with interventions that include threat and efficacy information to respond effectively to students' asthma.…”
Section: The Extended Parallel Process Modelmentioning
confidence: 99%
“…Several researchers have begun to extend the concept of personal susceptibility to articulate the ideas of indirect fear appeals (Morrison, 2005), and threat to others (Goie et al, 2010;Roberto & Goodall, 2009). Morrison focused on personal relationships, finding that men could be motivated to speak to women they care about regarding sexual assault through the use of indirect fear appeal messages.…”
Section: The Extended Parallel Process Modelmentioning
confidence: 99%